2015
DOI: 10.1002/2015je004857
|View full text |Cite
|
Sign up to set email alerts
|

NOxproduction and rainout from Chicxulub impact ejecta reentry

Abstract: The Chicxulub impact 66.0 Ma ago initiated the second biggest extinction in the Phanerozoic Eon. The cause of the concurrent oceanic nitrogen isotopic anomaly, however, remains elusive. The Chicxulub impactor struck the Yucatán peninsula, ejecting 2 × 1015 kg of molten and vaporized rock that reentered globally as approximately 1023 microscopic spherules. Here we report that modern techniques indicate that this ejecta generates 1.5 × 1014 moles of NOx, which is enough to cause the observed nitrogen enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Our approximation is thus reasonable, because much faster, strongly ablating meteoroids will have substantially higher peak mass fractions. In fact, a more recent modeling study [103] on the re-entry of spherules produced and ejected by the Chuxculub impact has shown that the NO mole fraction is consistent with the value adopted in our study. Consequently, the mass of produced NO is computed from 80 to 95 km within the volume corresponding to the initial radius of a bright meteor train.…”
Section: Methodssupporting
confidence: 92%
“…Our approximation is thus reasonable, because much faster, strongly ablating meteoroids will have substantially higher peak mass fractions. In fact, a more recent modeling study [103] on the re-entry of spherules produced and ejected by the Chuxculub impact has shown that the NO mole fraction is consistent with the value adopted in our study. Consequently, the mass of produced NO is computed from 80 to 95 km within the volume corresponding to the initial radius of a bright meteor train.…”
Section: Methodssupporting
confidence: 92%
“…To apply the aforementioned trace species transport model (Parkos et al, ), we must determine the diffusion coefficient. From Parkos et al (), DtūTM …”
Section: Resultsmentioning
confidence: 99%
“…Existing work by the aerospace community (Ahmadjian et al, ; Arnold & Coleman, ; Zahn & Murad, ) demonstrates that nonequilibrium plays a crucial role in the production yield of certain chemical species. This effect was shown to be important for NO production during the Chicxulub impact (Parkos et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This can happen in shockwaves, plasma environments, and detonations. [1][2][3] When the gas is perturbed from a local thermal equilibrium, intermolecular interactions try to return the system back to equilibrium. However, regions of nonequilibrium can persist in the flow if the local convection or reaction rates are comparable to the relaxation rates of the internal energy modes.…”
Section: Introductionmentioning
confidence: 99%